Potent and synergistic neutralization of human immunodeficiency virus (HIV) type 1 primary isolates by hyperimmune anti-HIV immunoglobulin combined with monoclonal antibodies 2F5 and 2G12. - Mascola, J R (1997)
Three antibody reagents that neutralize primary human immunodeficiency virus type 1 (HIV-1) isolates were tested for magnitude and breadth of neutralization when used alone or in double or triple combinations. Hyperimmune anti-HIV immunoglobulin (HIVIG) is derived from the plasma of HIV-1-infected donors, and monoclonal antibodies (MAbs) 2F5 and 2G12 bind to distinct regions of the HIV-1 envelope glycoprotein. The antibodies were initially tested against a panel of 15 clade B HIV-1 isolates, using a single concentration that is achievable in vivo (HIVIG, 2,500 microg/ml; MAbs, 25 microg/ml). Individual antibody reagents neutralized many of the viruses tested, but antibody potency varied substantially among the viruses. The virus neutralization produced by double combinations of HIVIG plus 2F5 or 2G12, the two MAbs together, or the triple combination of HIVIG, 2F5, and 2G12 was generally equal to or greater than that predicted by the effect of individual antibodies. Overall, the triple combination displayed the greatest magnitude and breadth of neutralization. Synergistic neutralization was evaluated by analyzing data from dose-response curves of each individual antibody reagent compared to the triple combination and was demonstrated against each of four viruses tested. Therefore, combinations of polyclonal and monoclonal anti-HIV antibodies can produce additive or synergistic neutralization of primary HIV-1 isolates. Passive immunotherapy for treatment or prophylaxis of HIV-1 should consider mixtures of potent neutralizing antibody reagents to expand the magnitude and breadth of virus neutralization.